Seed and seedling morphology of Eriotheca gracilipes (K.Schum.) A. Robyns - Porto, Rebeca Andrade; Coelho, Maria F.; Cabral, Carlos Eduardo Avelino; Lima, Jessica Patrícia Paula; Camili, Elisangela Clarete [UNESP] (Centro Universitario de Maringa, 2023)
Eriotheca gracilipes (K. Schum.) is a tree endemic to the Brazilian savannah. The knowledge of the morphological characteristics of the seeds is a tool for understanding and describing the germination process. The aim of the present study was to characterize seeds and seedlings of E. gracilipes in order to facilitate identification in the laboratory and in the field. For the description of the germination, four replicates of 25 seeds were used in rolls of moist paper. The water content of the seeds of E. gracilipes was 10.4% and the mass was 4,942,17 per Kg-1. The species E. gracilipes possesses fast germination, hypogea and phanerocotyledon with non symmetrical cotyledons and of different functions with the reserve of larger size than the cotyledon foliaceus. The seeds are light which favors dispersion by the wind. Seedlings can be used to identify the species and have heterofilia. The species can be used in programs to recover degraded areas due to their rapid formation of seedlings.
Morfologia de sementes e plântulas de Eriotheca gracilipes (K. Schum.) A. Robyns
Keywords: Cerrado; Characteristics of seeds; Germination; Malvaceae